“One thing led to another” - teenage pregnancy during COVID-19: a Zimbabwean case study - Tigashire Megan Hofisi; Chipo Hungwe (International Journal of Adolescence and Youth)
Teen pregnancy is common in Zimbabwe and is associated with health and socio-economic challenges. Drawing ideas from social disorganization and intersectionality theories, this study explores the perceived causes and consequences of teenage pregnancy in Kadoma, Zimbabwe, during COVID-19. Data were gathered from 10 purposively selected pregnant teenagers and teen mothers aged between 15 and 19. These young women were interviewed through semi-structured interviews and data were analysed using thematic analysis. Seven parents/guardians and 10 key informants were also interviewed. The causes of teen pregnancy have largely remained the same over time (poverty, lack of individual agency due to cultural and religious pressure and the influence of the media), although the COVID-19 pandemic heightened some of them and added one more – extended school closures. The consequences were identified as stigmatization, lack of support and school drop-outs. A holistic approach is needed to curb teenage pregnancy.